Effects of Cigarette Smoking in Adults - Chan, Lana Lan (MacEwan University Student eJournal, 2016)
First-hand cigarette smoking is known to result in adverse health effects in adults, influencing wellbeing physically and mentally. The most prevalent physical consequences are cardiovascular diseases, cancer of the throat and oral cavities, diseases of the bowel, eye, respiratory system, and reproductive system. Arguably, direct effects of tobacco smoking have been said to affect mental aspects of wellbeing such as depression, mood, and anxiety disorders. Undoubtedly smoking comes with many negative effects, but with implementation of smoking cessation strategies, it is possible to strengthen the overall health and wellbeing of smokers. As such, Health Canada recognizes the many health benefits associated with smoking cessation, by delivering health-promoting campaigns that strongly urge, it is not too late to quit.